Screening and identification of actinomycetes having antimicrobial activity isolated from marine organisms and sediment samples in Ly Son island, Quang Ngai - Thanh Hoa, Tran Thi; Hong Minh, Le Thi; Quyen, Vu Thi; Mai Anh, Nguyen; Mai Huong, Doan Thi; Van Minh, Chau; Van Cuong, Pham (Vietnam Journal of Biotechnology, 2020)
The discovery of bioactive compounds from marine microorganisms for drug development has been currently widely studied. In which marine actinomycetes are highlighted as a potential source in finding antibiotics as well as substances with biological activity in general. The objective of this study is to isolate and screen the actinomycetes strains with antibacterial activity from the marine environment. Sixty one actinomycetes were isolated from 80 samples of marine organisms and sediments collected from Ly Son Island, Quang Ngai. The strains were fermented in the A1 medium and the culture broths were extracted by ethyl acetate and vacuum rotary evaporation to produce crude extracts. Antimicrobial activity of the extracts were carried out on 7 strains of tested microorganisms, including three strains of Gram-negative bacteria (Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853, Salmonella enterica ATCC13076), three Gram-positive strains (Enterococcus faecalis ATCC29212, Staphylococus aureus ATCC25923, Bacillus cereus ATCC 13245), and yeast Candida albicans ATCC10231. The screening results showed that three strains with the highest antimicrobial activity (G330, G336 and G361) were capable of inhibiting 5 of the 7 tested microorganisms with Minimum Inhibitory Concentration (MIC) values ranging from 4 to 256 μg/mL, depending on each tested strain. Specifically, all three strains inhibited C. albicans ATCC10231 and three Gram-positive strains (E. faecalis ATCC29212, S. aureus ATCC25923, B. cereus ATCC 13245). In addition, G330 and G336 also showed the inhibitory activity to Gram negative strain S. enterica ATCC13076 with value of 256 µg/mL, G361 has a good inhibitory ability for E. coli ATCC25922 with MIC value of 8 µg/mL. The strains were identified by morphological and the 16S rRNA gene sequences. The results showed that 16S rRNA sequences of the strains had over 99% similarity to the 16S rRNA sequences on the GeneBank database, strains G336 and G361 belonged to the genus Salinispora, whereas strain G330 belonged to the genus Streptomyces. These results showed that marine environment has a great potential in solation of actinomycetes strains for the search for antibacterial substances as well as other biologically active compounds.